Diagnostic Yield of Upper Gastrointestinal Endoscopy in Children: A Three Years Experience - Joshi, Binita Gurubacharya; Ghimire, Madhu (Journal of Nepal Paediatric Society, 2020)
Introduction: Gastrointestinal disorders are very common in paediatric population. Upper Gastrointestinal Endoscopy procedures have increased dramatically worldwide and have contributed in identification of various gastrointestinal disorders along with therapeutic benefits. However, it is recently being established in paediatric population in Nepal and proper data is scarce. This study was aimed to assess upper gastrointestinal endoscopy with respect to its indications and diagnostic yield at a tertiary centre over a three years period. Methods: This is a retrospective observational study where data of all paediatric patients between the age group 0 - 15 years having various gastrointestinal problems who underwent upper gastrointestinal endoscopy from March 2013 - Feb 2016 in our centre were analysed. Results: Among 270 patients, males comprised 60% and females comprised 40%. Age range was 0 - 15 years and majority were from the age group between 10 to 15 years (66.2%). Most common indications for endoscopy were chronic abdominal pain (58.8%), acute epigastric pain (18.5%), followed by failure to thrive (7%). Abnormal findings were detected in 250 patients (92.5%); gastroduodenitis (28.14%), antral gastritis (18.51%), erosive gastritis (15.92%), duodenitis (9.25%), hiatus hernia (7.4%), varices (5.5%) were common findings. Histopathologically, chronic gastritis and duodenitis (72%) were common findings followed by acute gastritis and giardiasis. Among 80 patients who underwent RUT, 50% each had positive and negative results. Conclusion: Chronic abdominal pain remains common gastrointestinal problem in children. With the advent of upper gastrointestinal endoscopy various gastrointestinal problems can be identified and managed accordingly. Along with the facility of histopathology, diagnostic yield and outcome is further enhanced.